TI_GERICHTE 52.2018.103 vom 17. Januar 2018 , Licenza edilizia per una terrazza esterna al servizio di un esercizio pubblico - TI Tribunale d'appello (2018)
Licenza edilizia per una terrazza esterna al servizio di un esercizio pubblico